LEARNING FROM HISTORY: PAKU BUWANA II'S ATTEMPT AT RELIGIOUS MODERATION IN SERAT CEBOLEK - Permadi, Danur Putut; Yantari, Hanif Fitri; Taufiq, Muhammad (Jurnal Lektur Keagamaan, 2024)
Indonesia is home to teachings and manuscripts that advocate moderation in life. One such cultural manifestation is the Serat Cebolek manuscript, written by Yasadipura I. This manuscript narrates the theological conflict between Hajj Mutamakkin and Ketib Anom. The objective of this article is to examine the efforts towards religious moderation undertaken by Sunan Paku Buwana II, as depicted in the Serat Cebolek manuscript. This study employed library research, utilizing a biographical approach. Data was collected through documentation techniques, drawing from printed sources and texts pertaining to Serat Cebolek. The study reveals that Paku Buwana II’s decision to forgive Haji Mutamakkin exemplifies the characters of a moderate leader. The king pardoned Haji Mutamakkin’s actions, albeit with the stipulation that he refrain from disseminating his knowledge among the kingdom’s populace. In the context of Javanese ethical values, Sunan Paku Buwana epitomizes a “Ratu Adil” or a just ruler. This study reinforces the discourse on religious moderation, particularly through an exploration of historical contexts. The king’s attitude serves as a valuable exemplar for contemporary leaders grappling with the issue of religious fundamentalism in Indonesia.